'Holding mind in mind': the use of work discussion in facilitating early childcare (kindergarten) teachers' capacity to mentalise. Issue 1 (2nd January 2018) - Hover-Reisner, Nina; Fürstaller, Maria; Wininger, Antonia
ABSTRACT: In this article the method of Work Discussion is introduced as an instrument for improving the capacity for mentalization. The authors refer to a vocational training project with early child care teachers in kindergartens and a short case study is presented. The authors use this project to outline how work discussion was used to reflect on professional practice and the goals pursued by applying this method in the course of vocational training. The concept of 'mentalization' is defined and the paper discusses whether and how using work discussion can contribute to stimulating, developing or enhancing the early child care teachers' capacity mentalize.